THE INFLUENCE OF GREEN MARKETING ON PURCHASING DECISIONS WITH GREEN BRAND IMAGE AS A MEDIATION VARIABLE(Study of IKEA Consumers in Denpasar City) - Ni Made Widi Anjani; I Wayan Santika (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Companies are starting to increase their concern for the environment by starting to implement new trends in carrying out their marketing strategies related to environmental issues, namely by implementing green marketing concepts that are environmentally friendly or known as green marketing. Companies that apply the green marketing concept by producing environmentally friendly products are considered to have a green brand image because the company is considered to care about environmental sustainability. This research aims to determine the influence of green marketing on purchasing decisions with green brand image as a mediating variable. This research was conducted on IKEA consumers in Denpasar City and the number of samples in the research was 100 people. The research method used is quantitative. Data collection was carried out using a survey approach, where the research instrument used was a questionnaire. The data analysis techniques used in this research are validity test, reliability test, classical assumption test, path analysis and sobel test. The result of this research shows that green marketing has positive and significant influence on purchasing decisions, green marketing has a positive and significant influence on green brand image, green brand image has a positive and significant influence on purchasing decisions andgreen brand image able to mediate the influence of green marketing on purchasing decisions. The advice that can be given in this research is that IKEA is expected to always use environmentally friendly places to distribute its products, always look after good reputation for the environment and always offering quality and environmentally friendly products.